Towards Sustainable Ecotourism: Analyzing the Impact of Memorable Tourism Experiences and Tourist Satisfaction in Indonesia - Sari, Niken Permata; Sari, Utami Tunjung; Prastyanto, Anjas Nugroho; Hadi, Antonius Satria (Universitas Bangka Belitung, 2025)
This study aims to analyze the influence of Memorable Tourism Experiences and Tourist Satisfaction on Revisit Intention of tourists in Indonesia, especially in the context of ecotourism. With its diverse natural and cultural wealth, Indonesia has great potential to become a sustainable ecotourism destination. However, the sustainability of this sector requires a deeper understanding of the factors that influence tourists' intention to return. This study examines Destination Attractiveness, Service Quality, and Security Risk as the main determinants that influence tourist satisfaction and memorable tourism experiences. The methodology used involves collecting primary data with purposive sampling from 250 respondents who have visited ecotourism destinations. Data were analyzed using path analysis to test the relationship between variables. The results show that Destination Attractiveness and Service Quality significantly influence Memorable Tourism Experiences and Tourist Satisfaction, which in turn increases tourists' intention to revisit. This study provides important implications for destination managers and tourism industry stakeholders in developing effective strategies to increase tourist loyalty and support sustainable ecotourism development in Indonesia.